Generációs különbségek a szakszövetkezeti tagság körében (Egy kerekegyházi vizsgálat eredményei alapján) - Kovács, Teréz (Tér és Társadalom, 1987)
At the time of the 1961 collectivization wave in agriculture the formation of specialized cooperatives represented a midway between collective and individual farming. Specialized co-operatives pooled less individual property from theír members than full co-operatives. The joining farmers of the time (the member-farmers of today) have had to pay, however, a property contribution: 5 kg wheat per one unit plough-land expressed in golden crown and 10% of the value of grapes and fruits delivered. At the beginning, this property contribution was virtually the only source of capital expenditure in the specialized co-operatives but nowadays, with the aging of member-farmers, and the rapid development of non-farming auxiliary activites, it has a declining proportion. Until quite recently, specialized co-operatives were put at a disadvantage in the system of state taxation and subsidies in comparison with full agricultural co-operatives. In certain villages the managers of specialized co-operatives introduced non-farming auxiliary activities – in a skilful and veiled manner – earlier than it was the case in full co-operatives. At present, the most stable and the most profitable auxiliary plants are the fruit- and grape processing ones which represent a vertical integration of the activities. Our survey conducted in Kerekegyháza in the autumn of 1984 revealed some specific features of the local specialized co-operative named 'Kossuth'. Considering the yield of collective farming, the results of this co-op are below the average but with regard to the member-farmers' individual output, they are above the average. The members of the specialized co-operative in this village form distinct types with respect to their mode of farming and lifestyle. The first type is made of member-farmers who work individually. Their number is 700 and their average age is 67 years. The second major type: co-op members who work on the collective farm. Their number, taken together with the employees, who follow a similar way of life, is 350 and their average age is 36 years. Therefore, different modes of farming also represent a difference of generations. Those who are over 50 years old will continue – though under different circumstances – peasant farming, as long as they are physically able to. The 'peasant-bourgeois' undertakings between the two wars were, however, dissimilar to the undertakings of the new generation considered here. The peasant-bourgeois farmers knew more about farming than about entrepreneurship. They had an extensive agrarian experience and took pleasure in farming. Nowadays, the undertakings of farmers in the 30-49 age group are characterized by their prompt reactions to market-price fluctuation, the mechanization of manual work and the exact and quíck identification of the legel protection provided by the specialized co-operative itself. Three sub-types can be distinguished within this generation: Type 1: those who run a small 'traditional mixed' farm on a full-time basis; Type 2: those who have got a full-time job at a co-operative or state entreprise but also run a modern, specialized, household- or auxiliary farm. They are typically in the managerial staff; Type 3: those who work in industry or agriculture as semi-skilled or unskilled labourers and have got a small farm which consists of a modernized piggery and a subsistence vegetable garden. According to our survey, the 'preservation of agricultural traditions' has come to an end. The middle-aged and young entrepreneurs in Kerekegyháza are not the followers of the one-time model farmers. Formerly, even during the 1960s, the farmers deemed it to be worthwhile for them to work ín agriculture. But they did not expect their children to take over and run the family farm. Instead, they encouraged the new generation to get employed in industry and with this done, household farming is a supplementary activity now.